45S5 Bioglass®-based compositions containing alumina and strontium - Araujo, Mariana Silva de (2021)
Bioactive glasses are one of the pioneering material for biomedical applications and have been widely used for orthopedic and dental implant surfaces. However, their limited mechanical strength, low toughness, and wear resistance, as well as a high tendency to crystallize, have prevented their use as load bearing devices or that need to undergo thermal treatment during its production. In view of reduce its drawbacks the present research exposes the influence of 2 mol% of Al2O3 and 2 mol% SrO in 45S5 Bioglass®-based compositions. Four compositions were produced to elucidate the difference in how both oxides, separately and their synergy when together, affected the structure, thermal, bioactivity and mechanical behavior. Changes of medium-range structures were characterized by Qn distribution of Raman spectroscopy and evaluation of 31P, 27Al, 23Na and 29Si environment obtained by Magic angle spinning nuclear magnetic resonance (MAS-NMR). Despite Qn distribution was predominantly Q2 in all samples the composition criteria used enabled improved processing and stabilibity characteristics. The addition of Al2O3 and SrO promoted larger sinterability parameter (Sc) which indicates better sintering behavior, the glass stability against crystallization doubled (KH) compared to 45S5 and the processing window enlarged from 106 to 171. Fourier transform infrared (FTIR) analysis after in vitro bioactivity test indicates that 480 min of soaking in simulated body fluid (SBF) solution was sufficient for reconfiguration of the pre-existent features favoring the appearance of phosphate and carbonate phases. Scanning electron microscope (SEM) images and energy-dispersive X-ray (EDX) provided information upon the layers formed rich in calcium and phosphorous and silanol groups. The changes made in composition did not affect the reactivity but caused a decrease in maxima of pH. After overnight incubation, the minimum inhibitory concentration (MIC) was between 4 and 8 and minimum bactericidal concentration (MBC) was 8 ppm. The results suggested that both the different pH and rate of degradation may be the reason for the different antibacterial behavior of the samples. Moreover, all the compositions studied were considered non-cytotoxic by the neutral red uptake methodology. Considering changes in mechanical behavior the bending strength increased by 60% and toughness doubled. On the other hand, the wear resistance obtained against steel was found to be three times higher than 45S5. For the aforementioned reasons, the use of these new bioactive glasses might be a promising solution for the reconstruction of bone defects, as well as for the treatment and eradication of bone infections.